Implikasi Kebijakan UU Anti Terorisme Tahun 2015 Terhadap Ancaman Human Security Tunisia - Haqxyla, Aliyya; Sushanti, Sukma; Parameswari, AA Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This research aims to describe how The 2015 Anti-Terrorism Law can poses a threat to the human security of the Tunisian people by using qualitative methods. Researcher uses the concept of Human Security and Responsibility to Protect to examine the threats given during the implementation of the policy. This research then perceive that there are problematic articles within the law that have an impact on the emergence of violations of human rights in Tunisia which becoming a threat to their life, it’s then also becomes the reason for the international community to give their response to these issues through their Responsibility to Protect. Keywords: Tunisia, Anti-terrorism policy, Human Security, Responsibility to Protect